Lateral fold and partial nail bed excision for the treatment of recurrent ingrown toenails - Zhu, Xiaoqiang (e-Century Publishing Corporation, 2012)
BACKGROUND: Ingrown toenail is one of the most common nail complaints. Although some surgical treatments have been described for relapse cases, frequent recurrence of pain, infection, and poor cosmetic results prompted us to search for an appropriate treatment. OBJECTIVE: This study was aimed at evaluation of our surgical technique of lateral fold and partial nail bed excision for the treatment of recurrent ingrown toenails. MATERIALS AND METHODS: We retrospectively reviewed the charts of 138 patients who underwent surgery by lateral fold and partial nail bed excision from 2009 to 2011. The operative technique, results, and long-term outcomes were recorded. RESULTS: 131 patients were followed up. 121 patients (92.37%) were cured. 10 patients (7.63%) had recurrent problems in 12 digits (7.06%). Of these, only 6 patients underwent surgery again. CONCLUSIONS: Lateral fold and partial nail bed excision is a simple, safe, and effective technique for treatment of recurrent ingrown toenails with a low risk of relapse.